THE USE OF PICTURE SERIES TO IMPROVE WRITING SKILL OF EFL LEARNERS - Komang Ayu Sri Wahyuni; Ida Bagus Nyoman Mantra; Nengah Dwi Handayani (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
The study aimed at figuring out the improvement of the writing skill of the tenth-grade students of SMKN 1 Mas Ubud through Picture Series. Picture Series is a technique of teaching writing in this present study. The undertaking of the research was mainly based on the preliminary study. The subjects were the tenth-grade students of SMKN 1 Mas Ubud in the academic year 2019/2020. There were 30 subjects which consisted of 17 males and 13 females. The design was a classroom action research design. The research was carried out through implementing Picture Series in two cycles and obtained data were analyzed quantitatively from the pre-test, post-test 1, post-test 2; then qualitatively from the questionnaire. The result showed that there was a significant improvement of the subjects’ skill in writing narrative text, pre-cycle (58,10) up to cycle I then, it improved in cycle II (80,40). In addition, the questionnaire proved that the subjects’ responses toward the implementation of the Picture Series were positive during the teaching-learning process. In short, the study showed that the writing skill of the tenth-grade students of SMKN 1 Mas Ubud in the academic year 2019/2020 could be improved through Picture Series.